THE UTILIZATION OF BEHAVIORAL FINANCE MODELS IN ANALYZING INVESTMENT DECISIONS - Bagas Adi Prayoga; Wiwit Hariyanto (Antis Publisher, 2025)
Objective: This study analyzes the impact of student financial behavior on investment decisions using a Behavioral Finance model. Method: Data were collected through interviews and observations with a descriptive qualitative approach. Result: The findings show that financial behaviors, such as adherence to payment schedules, budgeting, and price comparison, significantly influence investment choices. Emotional and psychological factors, like status quo bias, risk aversion, and overconfidence, also affect decision-making, often leading to suboptimal outcomes. Interviews confirm that these factors frequently hinder rational choices. However, the study’s limitations include sample representation and generalizability. Novelty: This research contributes to understanding Behavioral Finance in investment decisions and highlights the need for better financial education, emphasizing how behavioral and psychological aspects shape students’ investment behaviors.